The value of the Ringgit and the indonesian Rupiah In the Sale and Purchase Transactions of the Village Community Aji YellowSebatik island Borders the Indonesian - Malaysian - Safriadi, Safriadi; Ardi, Ardi; Muhammad Yusuf, Andi (International Journal of Educational Research & Social Sciences, 2021)
The activity of the socio-economic society can be seen in the daily activities on the environment where the people live, especially people who live in the border area. The village Aji Yellow into the study site is located in Kabupaten Nunukan or commonly called the Island of Sebatik. People in Sebatik Island imposed a two currencies in the region, namely currency ringgit and indonesian rupiah. The purpose of this study untukmenjelaskan the value and meaning of the ringgit and the indonesian rupiah in the view of the Village community Aji Yellow;type-type of commodity goods traded; the practice of buying and selling transactions using the ringgit and the indonesian rupiah in the community of the Village Aji Yellow. The study used a qualitative method through interviews and participant observation. The results of the research show the value and meaning of the orientation of currency applied by the community in the Village of Aji Yellow which includes: historical aspects, ease of access, commodity, practical, security. Goods that becomes a commodity trading almost the entire starting from primary needs to tertiary. The value of the ringgit and the indonesian rupiah in the view of society is the result of consensus that can be beneficial in the social and cultural environment on the border of the two countries, Indonesia and Malaysia.